Bagaza Virus in Himalayan Monal Pheasants, South Africa, 2016–2017 - Steyn, Jumari (Emerg Infect Dis, 2019)
Bagaza virus (BAGV) has not been reported in birds in South Africa since 1978. We used phylogenetic analysis and electron microscopy to identify BAGV as the likely etiology in neurologic disease and death in Himalayan monal pheasants in Pretoria, South Africa. Our results suggest circulation of BAGV in South Africa.